Analisis Pengaruh Pendapatan Asli Daerah dan Dana Alokasi Khusus Terhadap Kemandirian Keuangan Daerah Kabupaten dan Kota di Provinsi Jawa Tengah Periode 2022-2024 - Saputra, Dellen; Maryono, Maryono (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to investigate the influence of Regional Original Revenue (PAD) and Special Allocation Funds (DAK) on the financial independence of regencies and cities in Central Java Province during the 2022–2024 period. Regional financial independence is a key indicator for assessing a local government's capability to fund its administrative operations without relying on central government transfers. Employing a quantitative research design, the study utilizes secondary data sourced from the official website of the Directorate General of Fiscal Balance (DJPK). A total of 35 regencies and cities were selected purposively as the sample. The analysis was conducted using panel data regression with a Fixed Effect Model approach, alongside classical assumption tests. All data processing and analysis were carried out using the EViews 12 software. Research findings reveal that locally generated revenue (PAD) exerts a positive and statistically significant impact on regional fiscal independence, with a regression coefficient of 0.234 and a significance level below 5%. In contrast, the Special Allocation Fund (DAK) demonstrates a negative and significant effect, indicated by a coefficient of -0.167. This suggests that excessive reliance on DAK tends to reduce a region’s fiscal autonomy. These findings underscore the strategic importance of optimizing PAD as a key driver for strengthening sustainable fiscal decentralization.